(untitled) (International Journal of Engineering and Computer Science, 2020)
This paper presents a novel mesh generation scheme of all quadrilateral elements over a linear polygonal domain. We first decompose the linear polygon into simple sub regions in the shape of quadrilaterals. These simple regions are then quadrangulated to generate first into a fine mesh of four node quadrilateral elements using bilinear transformations.We propose then an automatic quadrilateral conversion scheme. Each four node quadrilateral is converted to an 8-node,9-node,12-node ,16-node,17-node and 25-noded quadrilaterals by inserting the midside nodes appropriately. Examples are presented to illustrate the simplicity and efficiency of the new mesh generation method for standard and arbitrary shaped domains. We have appended two important MATLAB programs which incorporate the mesh generation scheme for the 17-noded complete Lagrange elements developed in this paper.Other MATLAB programs can be coded on similar lines. These programs provide valuable output on the nodal coordinates ,element connectivity and graphic display of the all quadrilateral meshes for application to finite element analysis.